Pengembangan Sistem Pembelajaran Berbasis Multimedia - Suryanto Suryanto; Sunda Ariana; Syahril Rizal (Training and Research Institute Jeramba Ilmu Sukses (TRI - JIS), 2020)
Currently the development of information technology has an important influence in the development of learning systems, one of which is technology in the multimedia field. Multimedia technology is an indispensable tool for the learning process. The use of text, images, audio, video, and animation in learning helps students to quickly understand learning material. Multimedia also provides opportunities for educators to develop learning methods so that they get maximum results. AMIK AKMI Baturaja is a computer college that has not fully utilized information technology in its learning, especially in the field of Multimedia. For this reason, researchers conducted this research for the development of learning at the Campus AMIK AKMI Baturaja. This study aims to produce a multimedia-based learning media at AMIK AKMI Baturaja which can be a driving force for student learning achievement. In this study using a research method of literature study, observation, questionnaires, and interviews. The media development method uses MDLC (Multimedia Development Life Cycle) which consists of six stages, namely concept (needs analysis), design (design), material collecting, assembly, testing, and distribution. . The result of this research is a multimedia-based learning system presented in the form of e-learning. This media is expected to have a positive influence in increasing student achievement and learning independence.